The Dysfunction of the Trabecular Meshwork During Glaucoma Course. Issue 3 (March 2015) - Saccà, Sergio Claudio; Pulliero, Alessandra; Izzotti, Alberto
<x xml:space="preserve">Abstract</x> Primary open angle glaucoma is a multi‐tissue disease that targets, in an ascending order, the trabecular meshwork, the optic nerve head, the lateral geniculate nuclei, and the visual cortex. Oxidative stress and vascular damage play major roles in triggering apoptotic cell loss in these tissues. Molecular alterations occurring in the ocular anterior chamber during the early course of glaucoma trigger this cell loss. These molecular events are mainly of endogenous origin and related to the long‐term accumulation of oxidative damages arising from mitochondrial failure and endothelial dysfunction. This situation results in decreased antioxidant defences in aqueous humour and apoptosis activation in trabecular meshwork cells as triggered by severe mitochondrial damage altering tissue function and integrity. The presence of neural proteins in glaucomatous aqueous humour indicate that a molecular interconnection exists between the anterior and the posterior chamber tissues. Trabecular meshwork and lamina cribrosa share a common neuro‐ectodermal embryological, which contribute to explain the interconnection between anterior and the posterior chamber during glaucoma pathogenesis. During glaucoma, proteins deriving from the damage occurring in endothelial trabecular meshwork cells are released into aqueous humour. Accordingly, aqueous humour composition is characterised in glaucomatous patients by the presence of proteins deriving from apoptosis activation, mitochondrial damage, loss of intercellular connections, antioxidant decrease. Many questions remain unanswered, but molecular events illuminate TM damage and indicate that trabecular cell protection plays a role in the treatment and prevention of glaucoma. J. Cell. Physiol. 230: 510–525, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company